Point Sweep Coverage in Wireless Sensor Networks Using Convex Hull Algorithm - Kaur, Gurbax; Sharma, Ritesh (International Journal of Computer Sciences and Engineering, 2025)
There are lots of applications where only periodic monitoring (sweep coverage) is sufficient instead of continuous monitoring. The main goal of sweep coverage problem is to minimize the number of mobile sensor nodes moving with uniform velocity required to guarantee coverage as per given sweep time. Sweep coverage problems are broadly categorized in three types depending on applications viz point sweep coverage, area sweep coverage and boundary sweep coverage. In this paper we have solved the problem of point sweep coverage, where a set of densely spaced points in the given region are periodically monitored using convex hull algorithm.